Self-Concept in Student Learning and Motivation Truant : Descriptive-Correlation Studies - Harahap, Erlina; Pardede, Nurhasanah (Universitas Muhammadiyah Metro, 2017)
This research is aimed describ the learning motivation and self-concept of students who truant. This study used a descriptive quantitative method. The research conducted by the students of SMAN 5 Padangsidimpuan in the period of 2015/2016 with the total of the population was 420 students. Amount of research sample was 36 students and had been chosen by using purposive sampling technique. An instrument employed in this study was a Likert-scaled questionnaire. Data were analyzed by using percentage technique and the relationship between the two variables was analyzed by using nonparametric statistic, that is Spearman’s Coefficient of Rank Correlation. Results of this research are just like the following: 1) participants’ level of achievement on self-concept of students who truant is about 69,8%, 2) participants’ level of achievement on learning motivation of students who truant is about 69,2%, and 3) correlation coefficient of self-concept and learning motivation of students who truant is about 0,581. Therefore, it can be concluded that students who truancy have very low self-concept and learning motivation, and there is a significant relationship between self-concept and learning motivation. The implication in guidance counseling services is to create a service program which can increase self-concept and be learning motivation of students who truant